Biography. (Contemporary Music Review, 2014)
A biography of Agostino Di Scipio, the Italian musical composer is presented. He was born in 1962 in Naples, Italy and studied at Composition and Electronic Music from the Conservatory of L'Aquila. He then enrolled at Computer Music at the Centro di Sonologia Computazionale (CSC) in University of Padova. He is a composer, sound artist, and scholar. During his tenure, his accomplishments include "Intermittence", "Modes of Interference", and "Sound and Fury".